2017
DOI: 10.3892/or.2017.6037
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell migration and invasion by miR‑29a‑3p in a colorectal cancer cell line through suppression of CDC42BPA mRNA expression

Abstract: The objective of this study was to determine the effect of miR‑29a‑3p inhibitor on the migration and invasion of colorectal cancer cell lines (CRC) and the underlying molecular mechanisms. miR‑29a‑3p was detected using reverse transcription-quantitative polymerase chain reaction (RT‑qPCR) in the CRC cell lines HCT11, CaCo2, HT29, SW480 and SW620. An invasive subpopulation designated SW480‑7 was derived from the parental cell line, detected by Transwell and Transwell Matrigel assays. Cytoskeleton Regulators RT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…It should be noted that the role of miR-29a-3p in CRC has also been reported. Down-regulation of miR-29a-3p can promote the invasion and migration of CRC cells, and it can repress the invasion and migration of cancer cells by reducing the expression of CDC42BPA [16]. We observed that in CRC tissues, the expression of TTTY15 and miR-29a-3p was notably negatively correlated.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It should be noted that the role of miR-29a-3p in CRC has also been reported. Down-regulation of miR-29a-3p can promote the invasion and migration of CRC cells, and it can repress the invasion and migration of cancer cells by reducing the expression of CDC42BPA [16]. We observed that in CRC tissues, the expression of TTTY15 and miR-29a-3p was notably negatively correlated.…”
Section: Discussionmentioning
confidence: 66%
“…The expression of miR-29a-3p is also significantly down-regulated in gastric cancer and its low expression facilitate the proliferation, migration and invasion of cancer cells [14]. There are also studies on the expression and mechanism of miR-29a-3p in CRC [15,16], but the research is still not perfect, and its upstream and downstream molecular mechanisms still need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…The above results show us the two sides of mi-29a. A further functional study has indicated that miR−29a−3p inhibits cell migration and invasion of a colorectal cancer cell line by suppressing CDC42BPA mRNA expression (30). In our other experiment, through gene sequencing, it was found that miR-29a-5p was highly expressed in neural stem cells and inhibited its differentiation into glial cells.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, PAK1 can be directly activated by interaction with Rho-related GTPases CDC42 and RAC1 86 . However, some miRNAs targeting these activators can also regulate the activity of PAK1, such as miR-142-3p and miR-4715-5p targeting RAC1 87 , 88 , and miR302-367, miR‑29a‑3p, and miR-15b targeting CDC42 48 , 89 , 90 . Other miRNAs perform other functions.…”
Section: Endogenous Upstream Regulators Of Pak1mentioning
confidence: 99%